An Unusual Cause of Acute Abdomen in Adults: Giant Cystic Lymphangioma of the Pancreatic Head. A Clinical Case and Literature Review - Ghatak, Supriyo; Ray, Sukanta; Sanyal, Sumit; Sonar, Pankaj Kr; Khamrui, Sujan; Basu, Keya; Ray, Sujay; Das, Kshaunish (JOP. Journal of the Pancreas, 2011)
Context Cystic lymphangioma of the pancreas presenting as acute abdomen in adults has not been reported before. Case report We report the case of a young man who presented with severe pain in the upper abdomen and abdominal swelling. On imaging, he was found to have a giant multiseptate cystic lesion occupying almost the entire abdomen anterior to the pancreas. On exploration, a cystic mass involving the head of the pancreas and densely adherent to the antrum, and the second and third parts of the duodenum was found and a classic Whipple pancreaticoduodenectomy was done. Histology revealed a diagnosis of cystic lymphangioma. Conclusion Cystic lymphangioma is a rare benign tumor of the pancreas and this is the first reported case in an adult presenting with acute abdomen. Though rarely diagnosed preoperatively, this entity should also be considered in the differential diagnosis of cystic lesions of the pancreas. Complete surgical excision is curative. Image: Operative photograph showing the tumor.